Antropologi Pendidikan Heideggerian dan Sumbangannya bagi Praksis Pendidikan Kita - Doni Koesoema Albertus (Arete, 2012)
The institution of education always regards with human formation to lead persons to grow up by assuming that every person is in his journey to perfecting himself. Any practice of institutional education depends much on the concept of anthropology of education. Heidegger sees that any individual has two dimensions i.e. empirical ego and transcendental ego. These two dimensions of ego stay in its unique relationship both with other individuals in the sphere of institutional education and with other things which are manifested to that ego in order to lead him to the truth. Search for truth of his existence as human being is the open way which in turn forces individual to become “being open” and “open being”. Education is a way of thought which involves human existence in its fullest sense.